A randomised controlled trial of postural interventions for prevention of musculoskeletal symptoms among computer users. Issue 7 (16th June 2005) - Gerr, F; Marcus, M; Monteilh, C; Hannan, L; Ortiz, D; Kleinbaum, D
Abstract : Aims: To examine the effect of two workstation and postural interventions on the incidence of musculoskeletal symptoms among computer users. Methods: Randomised controlled trial of two distinct workstation and postural interventions (an alternate intervention and a conventional intervention) among 376 persons using computer keyboards for more than 15 hours per week. The incidence of neck/shoulder symptoms and hand/arm symptoms during six months of follow up among individuals in the intervention groups was compared to the incidence in computer users who did not receive an intervention (comparison group). For individuals in the intervention groups, study staff adjusted workstations, where possible, and trained individuals to assume the intervention postures. Individuals reported musculoskeletal symptoms in a weekly diary. Participants who reported discomfort intensity of 6 or greater on a 0–10 visual analogue scale or who reported musculoskeletal symptoms requiring use of analgesic medication were considered symptomatic. Results: There were no significant differences in the incidence of musculoskeletal symptoms among the three intervention groups. Twenty two (18.5%) participants in the alternate intervention group, 25 (20.2%) in the conventional intervention group, and 25 (21.7%) in the comparison group developed incident arm or hand symptoms. Thirty eight (33.3%) participants in the alternate intervention group, 36 (31.0%) in the conventional intervention group, and 33 (30.3%) in the comparison group developed incident neck or shoulder symptoms. Compliance with all components of the intervention was attained for only 25–38% of individuals, due mainly to the inflexibility of workstation configurations. Conclusions: This study provides evidence that two specific workplace postural interventions are unlikely to reduce the risk of upper extremity musculoskeletal symptoms among computer users.